Cosamalón Aguilar, Jesús A. y José Carlos Rojas Medrano, ¡Qué cosa tan linda! Una introducción al estudio de la salsa en el Perú. Lima: Instituto de Etnomusicología de la Pontificia Universidad Católica del Perú, 2020, 174 pp. - Ramos Rodillo, Ignacio Alejandro (2020)
Preliminary research on Peruvian salsa and salsa in Peru, highlighting historical and conceptual elements such as the transnationality of certain musical genres, the formation of local scenes and markets, their roots and identity implications, etc., up to the present day and going back to the beginnings of tropical music in the country, around the 1920s.